2009
DOI: 10.1145/2492101.1555368
|View full text |Cite
|
Sign up to set email alerts
|

Optimal power allocation in server farms

Abstract: Server farms today consume more than 1.5% of the total electricity in the U.S. at a cost of nearly $4.5 billion. Given the rising cost of energy, many industries are now seeking solutions for how to best make use of their available power. An important question which arises in this context is how to distribute available power among servers in a server farm so as to get maximum performance. By giving more power to a server, one can get higher server frequency (speed). Hence it is commonly believed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 11 publications
1
106
0
1
Order By: Relevance
“…which consists of the cost caused by the queuing delay o j at the servers as well as the cost caused by the network delay h j from the sensors to the physical service provider and from the physical service provider to DSS s j . According to the queuing delay model in [5], [7], which can be easily extended to other models, the cost of queuing delay when serving DSS s j is…”
Section: System Modelmentioning
confidence: 99%
“…which consists of the cost caused by the queuing delay o j at the servers as well as the cost caused by the network delay h j from the sensors to the physical service provider and from the physical service provider to DSS s j . According to the queuing delay model in [5], [7], which can be easily extended to other models, the cost of queuing delay when serving DSS s j is…”
Section: System Modelmentioning
confidence: 99%
“…In order to determine how the provisioned power impacts future workload performance, the power budget planner of C-FCA-WA relies on the workload power utility function ( f utility ), which characterizes the workload performance under different server power budgets and workload intensities. 6 The power budget planner collects the future workload intensity estimates for all servers within the rack ({λ i (t + k) , k = 1, ..., P}). Based on this information, for each power capping period in the near future, the power budget planner uses the average server power budget ( 1 N P Rack (t + k)) and the average workload intensity within the rack ( 1 N ∑ N i=1 λ i (t + k)) to approximate the average workload performance f utility within the rack.…”
Section: Fuelmentioning
confidence: 99%
“…Many studies have shown a massive waste of power consumed by idle or under-utilized devices. On one hand, PMs that are utilized by VNF instances are not power-proportional, since they consume more than 50% of their maximum power when they are in idle state [5]. Therefore, to provide powerefficiency, one solution is to increase PMs resource utilization, which leads to using lower number of active PMs.…”
Section: Introductionmentioning
confidence: 99%